Knowledge and practice of clients on preventive measures of COVID-19 pandemic among governmental health facilities in South Wollo, Ethiopia: A facility-based cross-sectional study. - Reta Dewau; Tefera Chane Mekonnen; Sisay Eshete Tadesse; Amare Muche; Getahun Gebre Bogale; Erkihun Tadesse Amsalu (PLoS ONE, 2021)
Introduction Coronavirus-19 is a global health challenge and need an immediate action. Thus, understanding client's knowledge about SARS-COV2 causes, roots of transmissions, and prevention strategies are urgently warranted. Although there were global studies reported knowledge and preventive practices of COVID-19, but the information is not representative and inclusive for Ethiopia. Thus, the current study is done to identify the knowledge and the prevention strategies for COVID-19 among clients in South Wollo, Ethiopia. Methods An institutional based cross-sectional study was conducted from May 21 to 30, 2020 among clients seeking service in Dessie town health facilities. A total of 81 clients were included from the selected health facilities with simple random sampling technique. We developed measuring tools by adopting from World Health Organization and center for disease prevention recommendation manual for assessing service providers' knowledge and preventive practices. For data entry Epi-data 3.1 version was employed and further data management and analysis was performed using STATA Version 14. Student T-test and one way ANOVA were computed to see the mean difference in knowledge and practice between and among the group. Chi-square test was also done to portray the presence of association between different co-variants with client's knowledge and preventive practices. Results Findings of the study showed that more than half (56.8%) of the participants had good knowledge about its symptoms, way of spread and prevention of the virus. Furthermore, 65.4% of clients demonstrated five or more preventive practice measures of COVID-19. The mean preventive practice score with standard deviation was (4.75±1.28 from 6 components). In the current study, knowledge had no significant difference among sex, education status, and monthly income. However, COVID-19 transmission knowledge was significantly higher among urban residents. Thus, clients who were knowledgeable about way of transmission and symptoms of COVID-19 had significantly higher COVID-19 preventive practice. Conclusion Our findings revealed that clients' knowledge and preventive practice of COVID-19 were not optimal. Clients with good knowledge and urban residents had practiced better prevention measures of the pandemic, signifying that packages and programs directed in enhancing knowledge about the virus is useful in combating the pandemic and continuing safe practices.